Pelatihan dan Pendampingan Learning Management System (LMS) Pada SMK Negeri 1 Tambelang Kabupaten Bekasi - Fauzi, Ahmad; Miharja, Muhammad Najamuddin Dwi; Siswandi, Arif; Wangsadanureja, Miftah; Maulana Majid, Annisa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The industrial revolution 4.0 has an impact on every field, one of which is the development of the world of education. Developments in the world of education can be seen in learning methods, including teaching and learning processes that are currently easily accessible for teachers and students. In the field of education, new learning methods such as the Moodle-based Learning management system are used to facilitate the teaching and learning process, but there is no implementation of a learning management system to manage online learning activities at SMK Negeri 1 Tambelang, Bekasi Regency. In this service, the implementation of the learning management system was carried out at SMK Negeri 1 Tembelang, Bekasi Regency. The Learning Management System is proven to facilitate the teaching and learning process for teachers and students at SMK Negeri 1 Tambelang, Bekasi Regency.